El sentido del poder político existente dentro de la estructura del poder estatal en Colombia: una mirada desde el constituyente como potencia - Sabogal Murcia, Leonardo (2023)
This paper aims to extract two senses of political power that operate within the Colombian Constitution of 1991, based on the importance of the constituent, drawing from certain elements that make up a positive sense of political power as the primary and fundamental sense for the state and society of Colombia, while recognizing that th e dominant sense of power continues to prevail and is contrary to the very essence of the constitution in real terms.